Industrial Heritage and Local Identity: Comparative Insights from Colomadu and Zhujiadian - Nursanty, Eko; Rusmiatmoko, Djudjun; Krismawanti, Krismawanti (International Journal of Environment, Architecture, and Societies, 2025)
This study aims to examine the role of industrial heritage conservation in shaping local identity through a comparative analysis of two industrial sites: Colomadu in Indonesia and Zhujiadian in China. Using a qualitative approach, data were collected through archival research, field observations, and stakeholder interviews. The findings reveal that adaptive reuse has contributed to economic growth by attracting tourism and investments while fostering a blend of modernity and tradition. However, commercialization poses challenges to maintaining the authenticity of these heritage sites. In Colomadu, the transformation into a cultural and heritage center reflects regional pride and integration with modern tourism. Meanwhile, Zhujiadian’s as a cultural hub hasrevitalized local economies but raised concerns about preserving historical integrity. This study underscores the importance of a balanced approach to heritage conservation, honoring authenticity while addressing contemporary economic and lifestyle needs.